Overweight, obesity, and cardiovascular disease in heterozygous familial hypercholesterolaemia: the EAS FH Studies Collaboration registry - Elshorbagy, Amany; Vallejo-Vaz, Antonio J; Barkas, Fotios; Lyons, Alexander R M; Stevens, Christophe A T; Dharmayat, Kanika I; Catapano, Alberico L; Freiberger, Tomas; Hovingh, G Kees; Mata, Pedro; Raal, Frederick J; Santos, Raul D; et al. (European heart journal, 2025)
BACKGROUND AND AIMS: Overweight and obesity are modifiable risk factors for atherosclerotic cardiovascular disease (ASCVD) in the general population, but their prevalence in individuals with heterozygous familial hypercholesterolaemia (HeFH) and whether they confer additional risk of ASCVD independent of LDL cholesterol (LDL-C) remains unclear. METHODS: Cross-sectional analysis was conducted in 35 540 patients with HeFH across 50 countries, in the EAS FH Studies Collaboration registry. Prevalence of World Health Organization-defined body mass index categories was investigated in adults (n = 29 265) and children/adolescents (n = 6275); and their association with prevalent ASCVD. RESULTS: Globally, 52% of adults and 27% of children with HeFH were overweight or obese, with the highest prevalence noted in Northern Africa/Western Asia. A higher overweight/obesity prevalence was found in non-high-income vs. high-income countries. Median age at familial hypercholesterolaemia diagnosis in adults with obesity was 9 years older than in normal weight adults. Obesity was associated with a more atherogenic lipid profile independent of lipid-lowering medication. Prevalence of coronary artery disease increased progressively across body mass index categories in both children and adults. Compared with normal weight, obesity was associated with higher odds of coronary artery disease in children (odds ratio 9.28, 95% confidence interval 1.77-48.77, adjusted for age, sex, lipids, and lipid-lowering medication) and coronary artery disease and stroke in adults (odds ratio 2.35, 95% confidence interval 2.10-2.63 and odds ratio 1.65, 95% confidence interval 1.27-2.14, respectively), but less consistently with peripheral artery disease. Adjusting for diabetes, hypertension and smoking modestly attenuated the associations. CONCLUSIONS: Overweight and obesity are common in patients with HeFH and contribute to ASCVD risk from childhood, independent of LDL-C and lipid-lowering medication. Sustained body weight management is needed to reduce the risk of ASCVD in HeFH.
Keywords: obezita; Registries; hyperlipoproteinemie typ II; kardiovaskulární nemoci; Cholesterol, LDL; Humans; index tělesné hmotnosti; lidé středního věku; Body Mass Index; Overweight; dítě; registrace; prevalence; Child; Female; rizikové faktory; mladý dospělý; dospělí; Aged; senioři; lidé; Dyslipidaemia; Insulin resistance; Hyperlipoproteinemia Type II; LDL-cholesterol; Adiposity; Adult; ženské pohlaví; Cardiovascular Diseases; Male; Middle Aged; Atherosclerosis; Adolescent; Heterozygote; Cross-Sectional Studies; Young Adult; Prevalence; Obesity; heterozygot; mužské pohlaví; průřezové studie; nadváha; mladiství; Risk Factors